Tingkat Pengetahuan Masyarakat Tentang Pemanfaatan Sampah Rumah Tangga Menjadi Energi Terbarukan Biogas di Desa Sembalun Bumbung, Provinsi NTB - Rosyantita, Tania Tri; A'yunin, Intan Qurratun; Tri Putri, Geby Harlia; Rosmaliati (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The village of Sembalun Bumbung is one of the villages with the widest geographical area in the Sembalun District, East Lombok Regency, West Nusa Tenggara Province covering 15 hamlets. The significant number of hamlets and residents in the village poses a serious issue, namely, the problem of waste. The absence of temporary disposal sites and distant final disposal sites prompts the people of Sembalun Bumbung to dispose of their waste into the river. Socialization and education efforts are conducted among the community to encourage the separation of organic and inorganic waste and utilize them as a source of renewable energy, such as biogas from household waste (SRT) like vegetable scraps, leaves, and food leftovers. Biogas processing is carried out using simple digester tools. Socialization and education are implemented by bringing in speakers. Socialization involves distributing knowledge questionnaires to 25 respondents, which are then analyzed using Microsoft Excel and SPSS version 20. The results of the questionnaire analysis, using the Paired Simple Test method, yielded a value of 0.000 (<0.05). The conducted socialization and education have been successful in enhancing the community's knowledge regarding biogas and the separation of organic and inorganic waste.